Crystallographic and computational characterization and in silico target fishing of six aromatic and aliphatic sulfonamide derivatives - Anh Van Nguyen; Anh Thi Ngoc Vu; Andrey N. Utenyshev; Valeriy Tkachev; Nadezhda Polyanskaya; Dmitriy Shchevnikov; Magrarita Vasil’eva; Hieu Tran-Trung; Xuan Ha Nguyen; Olga V. Kovalchukova (Royal Society Open Science)
The molecular and crystal structures of six compounds containing sulfonamide moieties are described. It has been shown that the geometric parameters of the sulfonamide group depend little on the nature of the substituents. Their bond lengths and bond angles remain almost the same and are in good accordance with those known from the literature. In crystals, depending on the type of substituents the molecules exist in the form of either monomers or dimers joined by intermolecular hydrogen bonds involving sulfonamide fragments. Introduction of large substituents into the molecules changes the way of packing of the studied sulfonamides and decreases the number of intermolecular hydrogen bonds in the crystals. The value of this dihedral angle may affect the nature and strength of the intermolecular bonding of the species in crystals. In silico analyses predicted low toxicity and potential enzyme inhibition, along with antiprotozoal properties, suggesting these compounds as candidates against protozoan pathogens. Molecular docking confirmed inhibitory potential against trypanothione reductase, supporting antiprotozoal activity. Consequently, these compounds may serve as promising lead-like molecules for drug development targeting protozoan infections.